Development of an ELISA for the detection of autoantibodies to BP230 - Kromminga, Arno (Clinical immunology (Orlando, Fla.), 2004)
Bullous pemphigoid (BP) is an autoimmune subepidermal blistering disease associated with autoantibodies against the transmembrane hemidesmosomal protein BP180/collagen type XVII and the intracellular plaque protein BP230. The aim of the present study was to develop an ELISA system for the detection of circulating autoantibodies to BP230. We generated five overlapping cDNA constructs covering the entire length of BP230 and expressed them in baculovirus-infected Sf21 insect cells. ELISA reactivity against BP230 was found in 63% of 56 BP patients' sera; the specificity of the ELISA was 93%. Epitope mapping studies showed that the fragment representing the C-terminal portion of BP230 was by far the most frequent target within the molecule. This ELISA provides a useful tool for the detection of autoantibodies to BP230 in BP and other diseases associated with an autoimmune response to this protein